2012
DOI: 10.5296/emsd.v1i1.1623
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Design Team Attributes on Green Design Performance of Building Projects

Abstract: The design phase is the most important phase in determining the green performance of building projects. The performance of the design team is crucial. The growing importance of sustainability globally necessitates the inclusion of green criteria in the design team selection process. Therefore, a competent design teams is required to have a range of attributes as the basis for design decisions. The propose of this study to identify current green design performance level of design teams of building projects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…This is due to more than half of construction mistakes were caused by design insufficiency. Elforgani & Rahmat (2012) in their study stated that the roles and responsibilities of design professionals must be clearly stated, described and classified to ensure that the green practices that they are responsible for are developed, refined and applied from the beginning of the project. Danielle study's (as cited in Elforgani & Rahmat, 2012) indicates that if roles and responsibilities are not assigned, green initiatives might potentially be mistaken or cut out.…”
Section: Overview Of Green Buildingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to more than half of construction mistakes were caused by design insufficiency. Elforgani & Rahmat (2012) in their study stated that the roles and responsibilities of design professionals must be clearly stated, described and classified to ensure that the green practices that they are responsible for are developed, refined and applied from the beginning of the project. Danielle study's (as cited in Elforgani & Rahmat, 2012) indicates that if roles and responsibilities are not assigned, green initiatives might potentially be mistaken or cut out.…”
Section: Overview Of Green Buildingmentioning
confidence: 99%
“…The main issue to slow progress and reluctance in getting involved in green buildings is due to lack of awareness from construction practitioners such as consultants, contractors and clients (Abidin, 2009). Elforgani & Rahmat (2012) agree that lack of previous knowledge of a design team may contribute to a significant risk and affect to the overall project performance. Stewart et al as cited in Elforgani & Rahmat (2012) found that the key barriers of applying green building features are team knowledge and understanding of green rating systems.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, amongst all parties involved with the delivery of construction project, the client organization remains the only constant actor throughout the whole project lifecycle [20]. Therefore, the decision made by the clients influences the overall project performance [21]. These decisions influence the attitudes, behaviors and procedures of other parties that must be addressed, so as to achieve sustainability of the built environment [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, different factors are militating against the construction industry's sustainability initiatives [30][31][32][33][34][35][36]. The extant literature shows that most of these factors are client-related [21,[37][38][39]. Although these facts subsist, studies have not provided a practical means of dealing with the factors that affect the implementation of sustainable construction with respect to clients [40].…”
Section: Introductionmentioning
confidence: 99%